Synthesis of pH-Sensitive CMC /Chitosan Hydrogels by Gamma Irradiation - Kassem, N.F.; Negm, A.S.; Shukry, N.; El-Kalyouby, S. (Journal of Composites and Biodegradable Polymers, 2014)
Gamma irradiation was used with different dosages to prepare hydrogels from carboxymethyl cellulose (CMC) and chitosan (CHI) with different ratios, in presence of different methylene bisacrylamide (MBA) concentrations as a crosslinking agent. The hydrogels were characterized by FT-IR spectroscopy which confirmed complexation between carboxylic group in CMC and amino group in CHI. The swelling behavior in different buffers of different pH values was also studied. The results indicated the formation of network structure of pH-sensitive hydrogels. The CMC/CHI hydrogels were evaluated for the possible use in drug delivery field, in which the release profile of aspirin, as a drug model, was investigated. Scanning electron microscopy was carried out before and after aspirin release proving the drug release.